Success factors for new business start-up in Hong Kong: a study of the external networks of small business start-up - Ma, Victor Kee Kin (Curtin University, 2009)
Most small new firms face problems in surviving the gestation process and achieving a viable performance thereafter because of the very fact of their smallness and newness. Due to a lack of internal resources, entrepreneurs of small new firms find it necessary to seek resources from outside the firm through their external social network. The theory of social capital that prescribes valuable resources are embedded in social relations is, thus, particularly relevant to the small business start-up situation. The embedded resources within an external network are hypothesized to have a positive impact on the business performance of these new firms. The main objective of the present study is to empirically investigate the impact of external networks, and in particular the initial social network of entrepreneurs, to the success of small firm start-up in Hong Kong. The second objective is to determine whether there is any interaction effect of the entrepreneur’s networking capability with the external network structure on the start-up success of small Hong Kong firms.To carry out the research, this study offers a conceptual model linking initial network start-up success to initial network structure of start-up, and including an interaction effect from the entrepreneur’s networking capability. The study operationalizes social capital in four types of network constructs: network size, trustworthiness, network support and network diversity. A series of hypotheses relating to these four dimensions asserting external network determinants of the start-up success of small firms is posited. Other hypotheses which assert the interaction effect between an entrepreneur’s networking capability and the initial network structure on the success of small firm start-up, are also posited. A field survey, administered to 1,000 small Hong Kong firms of various industries, is used to gather the data. The questionnaire survey was developed in two languages – Chinese and English – to ensure a good level of understanding in the bilingual business environment of Hong Kong. Of the 1,000 questionnaires dispatched, a final sample of 89 small firms was used to empirically test the hypotheses using multiple regression analysis and multiple hierarchical regression analysis. Control variables such as entrepreneurs’ experiences and education prior to the firm start-up are included.Empirical results indicate that the verification of social capital theory’s prescription for start-up success cannot be supported unequivocally. The results suggest that some initial network conditions such as initial size of strong tie network, network support and network diversity are positively associated with some measures of start-up success, but trustworthiness of network ties and the size of weak tie network do not figure among them. No evidence is found to support that entrepreneurs’ networking capability can positively enhance the effect of the initial network structure on start-up success. Overall, the study raises some questions on the positive linear relationship of certain operationalized constructs such as network size and trustworthiness of social capital with start-up success. Following the findings of this research, future studies may choose to further investigate social capital theory on small start-up success by refining the operationalization of social capital, and verify other interaction effects of entrepreneurs’ networking capabilities.